Factors affecting the polychlorinated biphenyl signatures in serum of adults living in a highly polluted area in eastern Slovakia - Hlisníková, Henrieta; Kolena, Branislav; Trnovec, Tomáš; Richterová Bagratuni, Denisa; Patayová, Henrieta; Čonka, Kamil; Drobná, Beata; Rausová, Katarína; Tihányi, Juraj; Wimmerová, Soňa; Petrovičová, Ida; Nagyová, Miroslava; et al. (Frontiers in Public Health, 2024)
Over the years eastern Slovakia has been subject to consistent monitoring of high levels of polychlorinated biphenyls (PCBs) in both the environment and human populations attributed to the former production of PCBs at the Chemko Strážske plant. We aimed to investigate the extent to which dietary habits and residential location could affect the concentrations of PCBs in the blood serum samples of subjects. We enrolled 602 adult subjects from eastern Slovakia with an average age of 45.14 (±8.49) years. To determine the concentrations of 21 PCB congeners, we used solid phase extraction along with gas chromatography coupled with high-resolution mass spectrometry. Based on questionnaire data, the assessment of dietary habits and residential location was performed using score calculations and creating a map. Through principal component analysis, the 20 PCB congeners were classified into three groups: PC1, comprising highly chlorinated PCBs, and PC2 and PC3, consisting primarily of low chlorinated PCBs. Stepwise multivariate regression revealed positive and negative associations between PCB congeners represented by PC1-3 and scores related to the residential location and scores related to food consumption, respectively. We confirmed that levels of PCBs represented by PC1-3 increased with age. The geographical proximity to pollution sources proved to be a key contributing factor to the observed PCB levels in individuals residing in eastern Slovakia.